2022
DOI: 10.1590/1980-220x-reeusp-2021-0359en
|View full text |Cite
|
Sign up to set email alerts
|

Associated factors of neonatal near miss among newborns of adolescent mothers in Brazil

Abstract: Objective: To identify the associated factors of neonatal near miss among newborns of Brazilian adolescents and to compare their occurrence in young women aged 12 to 16 years and 17 to 19 years. Method: Cross-sectional, hospital-based study, using data from the study Nascer no Brasil (“Birth in Brazil”) on puerperal adolescents and their newborns in all regions of Brazil. Multiple and univariate logistic regression were employed to identify the associated factors of neonatal near miss. Results: The following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
1
1
0
4
Order By: Relevance
“…Thus, it is essential to pay more attention to women's health before pregnancy and help them get ready by means of health prevention and promotion actions and by properly diagnose and treat issues that may arise. Double or more pregnancies were associated with NNM by the present study, which matches the findings of the "Nascer no Brasil" research that also identified that kind of association in multiparous and nulliparous women 6 , in addition to another study based on data of the same research that used a hierarchical neonatal near miss model 20 and to a third study that showed an association with the outcome among adolescent mothers 21 . Thus, attention needs to be paid to multiple pregnancies and timely and essential care must be provided to this type of pregnancy, as studies show that it is not only associated with NNM, but also with neonatal death and a higher risk of prematurity and low birthweight 22 .…”
Section: Discussionsupporting
confidence: 90%
“…Thus, it is essential to pay more attention to women's health before pregnancy and help them get ready by means of health prevention and promotion actions and by properly diagnose and treat issues that may arise. Double or more pregnancies were associated with NNM by the present study, which matches the findings of the "Nascer no Brasil" research that also identified that kind of association in multiparous and nulliparous women 6 , in addition to another study based on data of the same research that used a hierarchical neonatal near miss model 20 and to a third study that showed an association with the outcome among adolescent mothers 21 . Thus, attention needs to be paid to multiple pregnancies and timely and essential care must be provided to this type of pregnancy, as studies show that it is not only associated with NNM, but also with neonatal death and a higher risk of prematurity and low birthweight 22 .…”
Section: Discussionsupporting
confidence: 90%
“…A inadequação do pré-natal é atribuída, principalmente, a questões sociais, contribuindo para desfechos neonatais negativos. (25,26) Na pesquisa Nascer no Brasil, dados semelhantes foram encontrados quanto à idade materna e ao pré-natal. A média de idade foi de 25,6 anos, 70,8% das mães tinham entre 20 e 34 anos de idade (variação entre 12 e 46), e 19,2% eram menores de 20 e 10,5% maiores de 35.…”
Section: Discussionunclassified
“…(18) Outro estudo associou a prematuridade extrema e o peso muito baixo às mães com menos de 20 anos, sendo 22,94% das mães do estudo. (26) Doenças preexistentes e intercorrências obstétricas são fatores preditores da morbimortalidade materna e perinatal. No que concerne às intercorrências, 136 (80%) prontuários sinalizaram sua ocorrência, com prevalência da doença hipertensiva (58; 35,8%).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…2,6,8,[12][13][14][15][16][17] Studies have primarily focused on deriving and validating the criteria to define SNM, 1,3,10 quantifying the prevalence of SNM and identifying risk factors in African, Asian and Latin American regions. 11,[18][19][20][21][22][23][24][25][26][27] Research is also lacking on a range of upstream social determinants of health inequity and their influence on SNM. 28,29 Living in a low-income area 12,[30][31][32][33][34][35] and being an…”
mentioning
confidence: 99%